JURIDICAL ANALYSIS OF POLYANDRY MARRIAGES REVIEWED FROM LAW NUMBER 1 OF 1974 ON MARRIAGE - Eti Mul Erowati; Ikama Dewi Setia Triana (Jurnal Komunikasi Hukum, 2022)
This legal research aims to determine the juridical analysis of polyandry marriages in terms of Law Number 1 of 1974 concerning Marriage. This research is a juridical-normative legal research. The research approach used is a statutory approach. The types of legal materials used are primary legal materials and secondary legal materials. The data collection technique used is a literature study technique. Furthermore, using data processing techniques that are deductive and analyzed using content analysis. The results showed that polyandry marriages are part of polygamy just like polygyny, but polyandry marriages are prohibited in Indonesia, while polygynous marriages are permitted under certain conditions. However, even so, polyandry marriages also still occur, although very rarely, which is caused by several factors, namely economic factors, distance factors and the unfulfilled inner living, age factors, lack of family harmony, lack of faith and weak understanding of religion as social control. and cultural factors. Based on a juridical analysis of Law Number 1 of 1974 concerning Marriage, it is not found any article that regulates permission for women or wives to have more than one husband or permission to do polyandry. The practice of polyandry is prohibited in Indonesia because it can have several impacts, namely the impact on offspring and the impact on the parties.